Toxicity assessment of parabens in Caenorhabditis elegans. (May 2020) - Nagar, Yogendra; Thakur, Ravindra Singh; Parveen, Tuba; Patel, Devendra Kumar; Ram, Kristipati Ravi; Satish, Aruna
Abstract: Parabens, the alkyl esters of p -hydroxybenzoic acid such as methylparaben (MeP), ethylparaben (EtP), propylparaben (PrP), butylparaben (BuP) are used as a preservative in food, personal care products (PCPs), and pharmaceuticals, due to their antimicrobial properties. Parabens are continuously released into the environment, during washout of PCPs, disposal of industrial waste from the pharmaceutical and paper industries. Parabens have been detected in the indoor dust, wastewater stream, surface water of rivers, and the marine system. Recent eco-toxicological data and the environmental presence of parabens, has raised concerns regarding the safety and health of environment/humans. Thus, to further understand the toxicity of parabens, the present study was carried out in the soil nematode and well established biological model organism Caenorhabditis elegans . In the present study, LC50 of MeP, EtP, PrP and BuP for 72 h exposures from L1 larva to adult stage was found to be 278.1, 217.8, 169.2, and 131.88 μg/ml, respectively. Further exposure to 1/5th of LC50 of parabens yielded an internal concentration ranging from 1.67 to 2.83 μg/g dry weight of the organism. The toxicity of parabens on the survival, growth, behavior, and reproduction of the C. elegans was found in the order of BuP > PrP > EtP > MeP. Worms exposed to parabens show significant down-regulation of vitellogenin genes, high levels of reactive oxygen species and anti-oxidant transcripts, the latter being concordant with nuclear localization of DAF-16 and up-regulation of HSF-1 and SKN-1/Nrf. Hence, parabens caused endocrine disruption, oxidative stress and toxicity in C. elegans at environment relevant internal concentration of parabens. Graphical abstract: Image 10156 Highlights: The order of toxicity of parabens in C. elegans is BuP > PrP > EtP > MeP. Parabens caused down-regulation of vitellogenins in C. elegans . Parabens induced ROS and antioxidant response in C. elegans . Cellular response to parabens is mediated through DAF-16, HSF-1, and SKN-1 transcription factors in C. elegans .